Canine and human sarcomas exhibit predominant FGFR1 expression and impaired viability after inhibition of signaling. Issue 9 (9th April 2014) - Schweiger, Nicole; Hauck, Marlene; Steinhoff, Heinrich; Sampl, Sandra; Reifinger, Martin; Walter, Ingrid; Kreilmeier, Theresa; Marian, Brigitte; Grusch, Michael; Berger, Walter; Holzmann, Klaus; Kleiter, Miriam
<x xml:space="preserve">Abstract</x> Fibroblast growth factor receptors (FGFRs) are important in malignant progression of several human epithelial tumors. However, little is known about FGFRs in canine or human soft tissue sarcomas. Thus, our aim was to investigate expression of FGFRs and their involvement in cell survival in sarcomas of both species. FGFR1–4 and FGFRL1 transcripts as well as IIIb/IIIc splice variants of FGFR1–3 were evaluated in 3 canine‐ and 6 human sarcoma cell lines and 19 spontaneous canine sarcomas by SYBRqPCR. FGFR1 protein expression was assessed by immunohistochemistry. Growth inhibitory effects of FGFR1 inhibitor PD166866 and dominant negative recombinant FGFR adenoviral expression constructs (dnFGFR) on tumor cell lines were analyzed. Profiling of multiple FGFR transcripts detected comparable co‐expression in most of human and canine sarcoma cell lines and canine tumor specimens. This indicates existence of closely related regulation mechanisms for FGFR expression in sarcomas of both species. FGFR1 with splice variant IIIc was consistently expressed with highest transcript levels. In 88% of the spontaneous tumor samples a heterogeneous FGFR1 protein expression was observed. Significant growth inhibition and cell death was seen after infection with dnFGFR1 in canine and human sarcoma cells, but not with dnFGFR3 and 4. PD166866 showed selective cytotoxicity with IC50 values between 12.1 and 26.4 μM. FGFR1 inhibition blocked ligand‐induced tyrosine phosphorylation of ERK1/2 mitogen‐activated protein kinase isoforms. This study emphasizes the important role FGFR1, especially splice variant IIIc, likely plays in sarcomas. Inhibitory small molecules could be of potential use for targeted therapy in aggressive sarcomas of both species. © 2014 Wiley Periodicals, Inc.